Cyberterrorism Today? Findings From a Follow-on Survey of Researchers. (3rd August 2022) - Macdonald, Stuart; Jarvis, Lee; Lavis, Simon M.
Abstract: This article reports on a survey of researchers designed to capture current perspectives on core questions around cyberterrorism. The survey—conducted in 2017 as a follow-on to an initial, 2012, exercise—focused on questions of definition, threat and response. By documenting our findings in each of these areas—and highlighting developments in the years between our surveys—we identify three particularly important trends. First, an increasing convergence around the core characteristics of cyberterrorism, albeit with continuing conceptual disagreements at the concept's penumbra. Second, increasing researcher concern with the threat posed by cyberterrorism, underpinned by a widespread view that this threat has increased, and a growing feeling that cyberterrorist attacks have now taken place. Third, support for a diversity of counter-measures to this threat, although perhaps counter-intuitively little suggestion that resort to exceptional or draconian measures is needed. In order to inform future research, the article concludes by detailing some of the major limitations, gaps and weaknesses within academic research to date as identified by our respondents.